A Review of the Evidence Base of Functional Assessment-based Interventions for Young Students Using One Systematic Approach. (August 2015) - Wood, Brenna K.; Oakes, Wendy Peia; Fettig, Angel; Lane, Kathleen Lynne
This review of the literature was conducted to explore the evidence base for functional assessment-based interventions (FABIs) for one systematic approach developed by Umbreit, Ferro, Liaupsin, and Lane (2007). Specifically, this review examined the evidence base for this systematic approach to FABI for young students by applying quality indicators and evidence-based standards. A secondary purpose was to identify the extent to which classroom teachers were involved in the FABI process. Twelve studies met the inclusion criteria of intervening with young students (i.e., preschool through third grade) with or at risk for disabilities using this one systematic approach to FABI. Although seven studies demonstrated positive effects and met all eight quality indicators (Council for Exceptional Children [CEC], 2014), indicating they were methodologically sound, these seven cases represented 14 students falling short of the recommended 20 participants (CEC, 2014). This review provides evidence for deeming this FABI model a potential evidence-based practice for use with young students. Limitations and future direction are discussed.